Hydrogen production via chemical looping reforming of coke oven gas - Kun Yang; Zhenhua Gu; Yanhui Long; Shen Lin; Chunqiang Lu; Xing Zhu; Hua Wang; Kongzhai Li (Green Energy & Environment, 2021)
Coke oven gas (COG) is one of the most important by-products in steel industry, and the conversion of COG to value-added products has attracted much attention from both economic and environmental views. In this work, we use the chemical looping reforming technology to produce pure H2 from COG. A series of La1-xSrxFeO3 (x = 0, 0.2, 0.3, 0.4, 0.5, 0.6) perovskite oxides were prepared as oxygen carriers for this purpose. The reduction behaviors of La1-xSrxFeO3 perovskite by different reducing gases (H2, CO, CH4 and the mixed gases) are investigated to discuss the competition effect of different components in COG for reacting with the oxygen carriers. The results show that reduction temperatures of H2 and CO are much lower than that of CH4, and high temperatures (> 800 °C) are requested for selective oxidation of methane to syngas. The co-existence of CO and H2 shows weak effect on the equilibrium of methane conversion at high temperatures, but the oxidation of methane to syngas can inhibit the consumption of CO and H2. The doping of suitable amounts of Sr in LaFeO3 perovskite (e.g., La0.5Sr0.5FeO3) significantly promotes the activity for selective oxidation of methane to syngas and inhibits the formation of carbon deposition, obtaining both high methane conversion in the COG oxidation step and high hydrogen yield in the water splitting step. The La0.5Sr0.5FeO3 shows the highest methane conversion (67.82%), hydrogen yield (3.34 mmol g−1) and hydrogen purity (99.85%). The hydrogen yield in water splitting step is treble as high as the hydrogen consumption in reduction step. These results reveal that chemical looping reforming of COG to produce pure H2 is feasible, and an O2-assistant chemical looping reforming process can further improves the redox stability of oxygen carrier.